Deep eutectic solvent-assisted synthesis of poly(furfuryl alcohol) grafted carbon nanotubes: a metal free electrocatalyst for non-enzymatic glucose detection. (15th August 2022) - Nguyen, Thi Hong Anh; Tran, Thao Quynh Ngan; Nguyen, Thi Nhat Thang; Khue Van, Thanh; Ngo, Dai-Hung; Kumar, Subodh; Cao, Xuan Thang
Abstract : We have synthesized a biomass-based metal-free electrocatalyst for glucose detection. It was observed that the nanocomposites having covalent interactions between the CNTs and PFA exhibited better performance than their analogous. Abstract : Metal-free catalysts are always desirable owing to their low cost and sustainable nature. In this report, we have synthesized a biomass-based metal-free electrocatalyst for glucose detection. The synthesis process includes two steps: (i) furfuryl alcohol (FA) polymerization into poly(furfuryl alcohol) (PFA) and (ii) covalent grafting of PFA onto the surface of CNTs via Diels–Alder (DA) reaction. Both the processes were performed in one pot using a choline chloride-based deep eutectic solvent (DES), which played an important role to achieve the maximum loading of PFA onto the CNT surface under ultra-sonication conditions. XRD, TGA, FT-IR, Raman spectroscopy, and SEM-EDX analytical results collectively confirmed the successful grafting of PFA. It was observed that the nanocomposites having covalent interactions between the CNTs and PFA exhibited better performance than their analogous and previously reported non-metal electrocatalysts for the electrocatalytic detection of glucose. These outcomes are important for designing and developing low cost metal-free electrodes by utilizing sustainable sources.